2022
DOI: 10.1097/aog.0000000000004835
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Corticosteroids and Neonatal Outcomes in Twins

Abstract: Evidence from nonrandomized studies suggests that antenatal corticosteroid treatment is associated with lower incidence of neonatal mortality and respiratory distress syndrome in twins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 37 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…In twins, evidence from a meta-analysis of non-randomized studies published in 2022 suggests that ACS are associated with a lower incidence of neonatal mortality and RDS, which was in agreement with the 2020 Cochrane meta-analyses of randomized controlled trials (RCTs) in multiples, but was not convincingly associated with other outcomes including IVH, NEC, bronchopulmonary dysplasia (BPD), periventricular leukomalacia (PVL), and retinopathy of prematurity (ROP) ( McGoldrick et al, 2020 ; Socha et al, 2022 ) probably due to the paucity of studies focusing on these secondary outcomes in twin pregnancy ( Table 1 ).…”
Section: Effects Of Acsmentioning
confidence: 68%
See 1 more Smart Citation
“…In twins, evidence from a meta-analysis of non-randomized studies published in 2022 suggests that ACS are associated with a lower incidence of neonatal mortality and RDS, which was in agreement with the 2020 Cochrane meta-analyses of randomized controlled trials (RCTs) in multiples, but was not convincingly associated with other outcomes including IVH, NEC, bronchopulmonary dysplasia (BPD), periventricular leukomalacia (PVL), and retinopathy of prematurity (ROP) ( McGoldrick et al, 2020 ; Socha et al, 2022 ) probably due to the paucity of studies focusing on these secondary outcomes in twin pregnancy ( Table 1 ).…”
Section: Effects Of Acsmentioning
confidence: 68%
“… Data abstracted from Socha et al (2022) . aOR, Adjusted odds ratios; RDS, Respiratory distress syndrome; IVH, Intraventricular hemorrhage; NEC, Necrotizing enterocolitis; BPD, Bronchopulmonary dysplasia; PVL, Periventricular leukomalacia; ROP, Retinopathy of prematurity.…”
Section: Effects Of Acsmentioning
confidence: 99%
“…Improving the developmental outcomes of twins is a high priority among the medical community. A collaborative effort on the effects of antenatal corticosteroids on the outcomes of multiple birth babies was undertaken by researchers in Canada, Australia and the United Kingdom (Socha et al, 2022). Records from MEDLINE, PubMed, EMBASE, and the Cochrane Library were reviewed from inception through August 12, 2021, and a metaanalysis was presented.…”
Section: Antenatal Corticosteroids and Twins' Neonatal Outcomesmentioning
confidence: 99%
“…1 While the risk of preterm birth is a much as ten times higher for multiple gestations compared with singletons, 2 the effectiveness of antenatal corticosteroids in this population is less certain. 3,4 A 2020 Cochrane review of randomised trials examining the effect of antenatal corticosteroids found only…”
mentioning
confidence: 99%
“…5 Although both reviews reported that antenatal corticosteroids reduced the risk of adverse newborn outcomes, confidence in these findings is limited by the potential for confounding in observational studies of drug effectiveness. 4,6,7 Current clinical practice guidelines in Canada and elsewhere recommend antenatal corticosteroid treatment for twins and higher order multiples, while also highlighting a need for more robust evidence of the effect of antenatal corticosteroids in these populations. [8][9][10][11] We sought to generate such evidence using a regression discontinuity design, which provides better control for confounding than conventional non-randomised studies that typically rely on regression adjustment alone (e.g.…”
mentioning
confidence: 99%